The Effect of Fermentation Time and Mass Variation of Saccharomyces Cerevisiae on The Characteristics of Virgin Coconut Oil from The Coconut Milk Fermentation Process - Tri Hutami, Anisa; Warsito, Evawanti A (Universitas Nahdlatul Ulama Surabaya, 2024)
Virgin coconut oil is one of the processed coconut products that has many benefits. Virgin coconut oil can be produced through extraction, centrifugation, and fermentation processes. In this study, virgin coconut oil was made by fermentation using baker's yeast (Saccharomyces cerevisiae). This study aims to determine the effect of fermentation time and mass variation of Saccharomyces cerevisiae used on the characteristics of virgin coconut oil produced. The process of making virgin coconut oil in this study is to separate skimmed water from coconut milk. Skimmed steering is mixed with Saccharomyces cerevisiae with variations of 0, 1, 1.5, and 2 grams, with fermentation durations of 12, 18 and 24 hours. The resulting virgin coconut oil is then analyzed to determine the iodine, peroxide, and acid numbers. From the results of the study, it is known that there is no relationship between the duration of fermentation and the mass of yeast Saccharomyces cerevisiae in the manufacture of virgin coconut oil from coconut milk against iodine number. The peroxide number for all variables of fermentation duration and yeast mass is 2 meq/kg. The acid number tends to increase with the length of fermentation, with the highest value being 0.6% at 24 hours fermentation time and the yeast mass of Saccharomyces cerevisiae 1.5 grams.